Tradition of Buka Luwur in Sunan Kudus Grave as a Social Cohesiveness of the Ancient Village in Kudus-Central Java - Moh Rosyid (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2022)
This article presents the meaningfulness of the tradition of Buka Luwur (a cloth covering the grave of Sunan Kudus) to the residents of Kauman Village, Kota sub-district, Kudus, Central Java, an ancient village in. The study’s data were obtained through interviews, observations, and literature reviews and analyzed using a descriptive-qualitative approach. The study found that Sunan Kudus, the first Islamic preacher in Kudus, has been respected by the residents of Kauman Village through the annual tradition called Buka Luwur (replacing the Luwur with a new cloth every Muharam/Sura month). The Foundation Functionary of Menara Mosque, Sunan Kudus Grave, and the residents of Kauman Village perform the tradition. The event series is very dynamic, beginning with the ritual abstersion of keris and two spears, the legacies of Sunan Kudus, the distribution of Sura porridge and Jangkrik rice, Islamic Art Attraction, and the replacement of old luwur with the new one having various motifs, i.e., jasmine, unthuk banyu, kompol, and wiru which have symbolic meanings. The old luwur are cut into pieces and shared with the residents of Kauman Village and the attending guests. The tradition is conserved to respect the trace of preaching (dakwah) of Sunan Kudus. Sociologically, the residents of Kauman Village preserve this tradition because it has a normative dimension and brings about solidarity and voluntariness, as well as the value of cultivating a life-appreciating character. Therefore, the tradition of Buka Luwur as a basic necessity of every resident of Kauman Village has given the impact of the birth of a routine activity in the village, which is considered by the public as an exclusive and individualistic activity. However, the stigma is refuted by cultural facts.